2021
DOI: 10.3389/fphys.2021.637790
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of Airway Epithelial Tight Junctions in Asthma Under High Airway Pressure Is Probably Mediated by Piezo-1

Abstract: Full functioning of the airway physical barrier depends on cellular integrity, which is coordinated by a series of tight junction (TJ) proteins. Due to airway spasm, edema, and mucus obstruction, positive end-expiratory alveolar pressure (also termed auto-PEEP) is a common pathophysiological phenomenon, especially in acute asthma attack. However, the influence of auto-PEEP on small airway epithelial TJs is currently unclear. We performed studies to investigate the effect of extra pressure on small airway epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The damage of the cellular barrier integrity in our disease models was shown in the low electrical resistance value in comparison to the healthy models. In addition, the dynamic co-culture of DHBE and NHLF (CNBio DHBE-NHLF) had discontinuous tight junctions, which was consistent with the previous finding in in vitro asthma models [24,36]. The cross-section histological images of this disease model exhibited overproduction and hypertrophy of goblet cells, and a reduction in the number of cilia.…”
Section: Discussionsupporting
confidence: 89%
“…The damage of the cellular barrier integrity in our disease models was shown in the low electrical resistance value in comparison to the healthy models. In addition, the dynamic co-culture of DHBE and NHLF (CNBio DHBE-NHLF) had discontinuous tight junctions, which was consistent with the previous finding in in vitro asthma models [24,36]. The cross-section histological images of this disease model exhibited overproduction and hypertrophy of goblet cells, and a reduction in the number of cilia.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that the expression of TJ proteins such as claudin-1, occludin and ZO-1 is significantly reduced in patients with asthma and upper respiratory diseases such as nasal polyps and chronic rhinosinusitis (56,57). Claudin-18 expression, a TJ protein required for maintaining the integrity of the airway epithelial permeability, was also lower in asthmatics compared to healthy controls (58,59).…”
Section: Epithelial Barrier Hypothesismentioning
confidence: 99%
“…Piezo channels are large proteins containing multiple transmembrane domains, with no known homology to any other proteins [19]. Activation of these channels induces calcium influx and regulates various calcium-dependent cellular activities [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insight into the Yoda1-induced effects on lens clarity and myosin II activity, we determined the activity of lens calpain, which is calcium dependent, since Piezo1 activation by Yoda1 is expected to increase calcium influx [26,28,29]. Lenses treated with 10 µ M Yoda1 for 24 hr exhibited a significant increase (of ~69%, n = 5) in calpain activity compared to the control lenses (Figure 6A).…”
Section: Yoda1 Treatment Induces Calpain Activity and Membrane Protei...mentioning
confidence: 99%